Studying Drug Delivery Applications Of Biopolymer Modified With Nanoparticles - Dr. Barun Ranjan Sarkar, Mr. Yadvendra Singh Thenuan (Drugs and Cell Therapies in Hematology, 2021)
Pharmaceutical formulation development involves various components in addition to the active pharmaceutical ingredients. In recent years, excipient development is become core area of research in pharmaceutical drug delivery because it influences the formulation development and drug delivery process in various ways. Biopolymers are choice of research as excipient because of its low toxicity, biodegrability, stability and renewable nature. Recent research and developments in the field of biopolymers direct the successful formulations of various novel and smart drug delivery devices with enhanced therapeutic efficacy, better patient compliances, and cost-effectiveness. In this chapter, biopolymers and their uses in drug delivery have been comprehensively reviewed.